Embedding lattice structures into ship hulls for structural optimization and additive manufacturing - Armanfar, Arash; Tasmektepligil, A. Alper; Kilic, Recep Tayyip; Demir, Serdar; Cam, Serhat; Karafi, Youness; Majd, Badr Abou El; Gunpinar, Erkan (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
Additive manufacturing (AM) has been making inroads into the shipbuilding industry. The maritime sector has recognized the potential benefits of AM in terms of cost savings, design flexibility, and rapid prototyping. Lattice structures, known for their vast applications in AM and associated benefits like lightweight design, energy efficiency, and improved material usage, serve as a focal point in this shifting landscape. This paper presents a pioneering approach to integrating lattice structures into shipbuilding via AM, specifically for supporting ship volumes. The method introduces algorithms to create both conformal and uniform lattice structures for structural optimization. According to the case studies in this work, ship models with lattice structures have superior structural properties compared to conventional support elements.
Keywords: Additive manufacturing; Lattice structure; Structural optimization; Ship hull; ELEMENT; DESIGN; Engineering; Oceanography